Boundary Value Analysis Testing Techniques on Learning Management System Applications - I Putu Astya Prayudha; Rukmi Sari Hartani; Yoga Divayana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2019)
Application of Learning Management System of Lampung State Polytechnic (LMS Polinela) is an elearning application developed as an alternative teaching media that aims to complement existing teaching media to help students learn independently so that learning outcomes are more optimal and efficient. This study uses a black box testing boundary value analysis technique in testing the Polinela LMS application. This boundary value analysis technique works by determining the upper and lower limits of the data to be tested, after which the data is inputted to the Polinela LMS application. The results of the review of the journal from Zuriati et al with the title